The Concept of Lie and Its Identification in Criminal Proceedings - Olegovich Antonov, Igor (2021)
In today's Russian environment, special attention in the work of preliminary investigation agencies is paid to the development and implementation of the latest methods and techniques for countering criminal behaviour. Essential to the timely and rapid detection of a crime and to the objective and comprehensive investigation of criminal cases is the high professionalism of the staff of preliminary investigation agencies, as well as their skills and abilities in practical work, which are undoubtedly based on scientific research on ways to identify criminal acts, expose guilty persons and prevent them from evading punishment. One form of counteracting the investigation of a criminal case is the giving of false testimony by subjects of criminal proceedings during questioning and face-to-face confrontation. This paper presents the theoretical basis for the diagnosis of lies, reveals the concept of lies, its main types, tactical features of the recognition of lies in the production of individual investigative actions; it also considers the problem of evaluating the truthfulness of testimony taking into account the features of personality of a person.